2020
DOI: 10.1016/j.artmed.2020.101820
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of sepsis utilizing deep learning on electronic health record event sequences

Abstract: Background: The timeliness of detection of a sepsis incidence in progress is a crucial factor in the outcome for the patient. Machine learning models built from data in electronic health records can be used as an effective tool for improving this timeliness, but so far the potential for clinical implementations has been largely limited to studies in intensive care units. This study will employ a richer data set that will expand the applicability of these models beyond intensive care units. Furthermore, we will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 36 publications
5
76
1
Order By: Relevance
“…The results of the literature search, including the numbers of studies screened, assessments for eligibility, and articles reviewed (with reasons for exclusions at each stage), are presented in Figure 1. Out of 974 studies, 22 studies met the inclusion criteria [Abromavičius et al, 2020, Barton et al, 2019, Bloch et al, 2019, Desautels et al, 2016, Futoma et al, 2017b, Kaji et al, 2019, Kam and Kim, 2017, Lauritsen et al, 2020, Lukaszewski et al, 2008, Mao et al, 2018, McCoy and Das, 2017, Moor et al, 2019, Nemati et al, 2018, Reyna et al, 2019…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the literature search, including the numbers of studies screened, assessments for eligibility, and articles reviewed (with reasons for exclusions at each stage), are presented in Figure 1. Out of 974 studies, 22 studies met the inclusion criteria [Abromavičius et al, 2020, Barton et al, 2019, Bloch et al, 2019, Desautels et al, 2016, Futoma et al, 2017b, Kaji et al, 2019, Kam and Kim, 2017, Lauritsen et al, 2020, Lukaszewski et al, 2008, Mao et al, 2018, McCoy and Das, 2017, Moor et al, 2019, Nemati et al, 2018, Reyna et al, 2019…”
Section: Study Selectionmentioning
confidence: 99%
“…Depending on the definition of sepsis used, and whether subsampling of controls was used to achieve a more balanced class ratio (facilitating the training of machine learning models), the prevalence of patients developing sepsis ranged between 6.2% and 63.6% ( Figure 2). One study did not report the prevalence [Lauritsen et al, 2020]. Concerning demographics, 9 studies reported the median or mean age, 12 the prevalence of female patients, and solely 1 the ethnicity of the investigated cohorts (Supplementary Table 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [4] proposes a deep learning-based early detection method which learns features by itself from clinical time-series data. It overcomes the shortcomings of machine learning using a deep learning approach on a diverse multicenter dataset.…”
Section: Introductionmentioning
confidence: 99%
“…rtificial Intelligence (AI) is capable of predicting acute critical illness earlier and with greater accuracy than traditional early warning score (EWS) systems, such as modified EWSs (MEWSs) and sequential organ failure assessment scores (SOFAs) [1][2][3][4][5][6][7][8][9][10][11][12][13] . Unfortunately, standard deep learning (DL) that comprise available AI models are black-box predictions that cannot readily be explained to clinicians.…”
mentioning
confidence: 99%